The Relationship of Adolescent Knowledge About The Three Basic Threats Of Adolescent Reproductive Health (Triad Krr) With Adolescent Attitudes To Reproductive Health In Smk Negeri 1 Tuhemberua - Jernihati Krisniat Harefa (Science Midwifery, 2022)
The problem that occurs in adolescents today is delinquency committed by teenagers who have begun to shift to things that are considered far beyond reasonable limits such as consuming alcohol, promiscuity that results in sexuality, HIV/AIDS, and drug abuse. Research purposesUTo find out the Relationship between Adolescent Knowledge About Three Basic Reproductive Health Threats (TRIAD KRR) With Adolescent Attitudes Towards Reproductive Health. Research design: analytic with cross sectional approach. Population: all youth of SMK Negeri 1 Tuhemberua as many as 119 people. Sample: 54 people with simple random sampling technique Instruments: questionnaire sheet and checklist sheet. Data analysis: chi square statistical test. Research results: Majoritylack of knowledge as many as 26 people (48.1%), and a minority of good knowledge as many as 10 people (18.6%).The majority of negative attitudes were 31 people (57.5%), andminority positive attitude as much as23 people (42.5%). Conclusion: there is a relationship between adolescent knowledge about the three basic threats to adolescent reproductive health (TRIAD KRR) with adolescent attitudes towards reproductive health with p <(0.000). Suggestion: It is recommended for adolescents to always be active to seek more information about the three basic threats to reproductive health (TRIAD KRR) so that they can increase the knowledge and insight of adolescents and can apply it in their lives.